FORMING THE SKILLS OF ARTISTIC PERCEPTION OF FINE ART WORKS IN STUDENTS (Multidisciplinary Journal of Science and Technology, 2024)
Knowledge, skills and abilities are not the ultimate goal of education, but they are a means of developing the individuality of the student, a creative person will show a creative approach in all activities in the future.